Fellow Prof. Dr. Stephen Brown in conversation with Prof. Dr. Thoko Kaime - Brown, Samuel T.; Kaime, Thoko (Cluster Conversations, 2023)
In this episode, Cluster fellow Prof. Dr. Stephen Brown from the University of Ottawa talks with his host Prof. Dr. Thoko Kaime about the situation of the LGBTQ community on the African continent and his project "Strategic Litigation and the Decriminalization of Homosexuality in Africa" which he is currently working on during his fellowship at the Cluster of Excellence.